Post Construction Effectiveness of Kathmandu-Naubise Alternative Road - Bhatta, Anjana (Journal of Advanced College of Engineering and Management, 2016)
Transportation is the backbone of the economic development of any developing country. Therefore, Nepal has emphasized on the construction of new roads both in the rural and urban areas. But there are various types and degrees of environmental problems associated with the construction of roads in Nepal. Kathmandu-Naubise Alternative Road has been taken in the case study for the research work. The project directly deals with the Twelve Environmental issues and their performance indicators which are contain in EMAP. This study emphasizes on the mitigation measures implementation in the project. This study has evaluated the degree of effective implementation of mitigation measures. The study has evaluated the arrangement in the project design and implementation aspects. It is concluded that the enforcement in the implementation is the key to the success of the project. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 25-33